UWRF CAFES internship program evaluation,- 2013 - Trechter, David; Parks, Denise (My University, 2013)
The motivation for this study was to evaluate intern experiences of the College of Agriculture, Food and Environmental Sciences (CAFES) students at the University of Wisconsin-River Falls (UWRF). The CAFES Internship Office wanted to understand and improve the internship experience of CAFES students.
58 p.
Keywords: College students; Students; University of Wisconsin-River Falls; College of Agriculture, Food and Environmental Sciences; University of Wisconsin-River Falls. College of Agriculture, Food and Environmental Sciences; University of Wisconsin-River Falls--Students; Internship program; Internships; College students--Wisconsin--River Falls